(untitled) (CIPEEX, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition that causes chronic airway obstruction and inflammation in both the lungs and the systemic circulation. Systemic inflammation in COPD is associated with a worse prognosis and an increased risk of complications such as cardiovascular diseases and sarcopenia. Although it is known that inflammation plays a central role in the progression of COPD, the relationship between nutritional status and the severity of inflammation, as well as the effects of protein supplementation, are not yet fully understood. This study aims to investigate the influence of nutritional status on pulmonary and systemic inflammation in patients with severe COPD, as well as to evaluate the impact of Whey Protein supplementation on modulating these inflammations. The research will involve 100 patients with severe COPD, who will be divided into groups, with some receiving Whey Protein. Nutritional assessments and analyses of inflammatory markers will be conducted before and after the intervention. It is expected that protein supplementation will improve inflammation indices and the quality of life for patients, presenting significant market potential given the prevalence of COPD among the elderly and the absence of specific supplements on the market to treat inflammation associated with this disease. The study may result in the publication of a scientific article confirming the effectiveness of Whey Protein in this context, opening new treatment possibilities for patients with severe COPD.